Unilateral lower motor neuron-type of facial palsy following snake bite presumably due to Krait (Bungarus Caeruleus) - Verma, S; Kumar, K; Arvind, S; Khadwal, A (Journal of Nepal Paediatric Society, 2012)
We describe an unusual case of snake bite presumably due to Krait (Bungarus Caeruleus) in a 12-year-old child from Mohali, Punjab. He presented with a history of bite behind his left ear, while he was sleeping at night on floor. He had bilateral ptosis, dysphonia initially, which progressed gradually to cause respiratory paralysis. Child was managed with antisnake venom, ventilation and other supportive measures. He recovered gradually, but persisted to have lower motor neuron paralysis of left facial nerve, which was noted post extubation. This uncommon presentation could be because of exposure of the facial muscles to the venom, spreading directly from the injection site and destroying the nerve terminals of facial nerve in the muscle tissue. At three months follow-up, child showed complete recovery. Facial nerve involvement following snake bite, which usually has a good prognosis, remain an uncommon presentation in paediatric age group. J Nepal Paediatr Soc 2012;32(2):184-186 doi: http://dx.doi.org/10.3126/jnps.v32i2.5824